Prevalence of sickle cell disease and sickle cell trait among children below 17 years of age attending Entebbe regional referral hospital in Wakiso district. A cross-sectional study. - Ngoobi, Lenard; Ssekitoleko, Anthony; Ssemuwemba, Franscisco; Nansereko, Hasifah; Nalubega, Jane Frank; Naggulu , Immaculate Prosperia (Student’s Journal of Health Research Africa, 2026)
Background: Sickle cell disease (SCD) is a genetic disorder that affects the shape of hemoglobin in the red blood cell, leading to the formation of a sickle shape. This study aims to determine the Prevalence of sickle cell disease and sickle cell trait among children below 17 years of age attending Entebbe Regional Hospital, Wakiso district, Uganda. Methods: This was a prospective cross-sectional study conducted at Entebbe regional referral hospital, which included 100 respondents who were selected using a purposive and convenience sampling technique, and data were collected prospectively by administering researcher-guided questionnaires. Results: The study participants, 55% (55/100), were female, and the age range of respondents was 0– 17 years, 45.0% (45/100) were aged 6-11 years. The Prevalence of sickle cell disease and sickle cell trait among respondents was 19.0% (19/100), with 6% (6/100) respondents found having the homozygous form, HbSS, and 13% (13/100) found having the heterozygous form, HbAS. 86% (86/100) of the respondents had heard about sickle cell, and the majority, 92% (92/100) of the parents had children that had never been screened for sickle cell, with only 8% (8/100) of the children ever screened. 39% (39/100) of the parents reported knowing the cause of sickle cell disease, with the majority, 61% (61/100), not knowing how SCD is caused. 65% (65/100) of the parents of respondents reported that sickle cell is transmitted from parent to child, 17% (17/100) did not know how SCD is transmitted. Conclusions: The prevalence of sickle cell disease and sickle cell trait was high, while the majority of the participants lacked knowledge about sickle cell screening. Recommendations: There is a need for health facilities to scale up screening services for sickle cell disease in the community so as to enable early diagnosis and treatment of the disease and reduce morbidity and mortality.